In Assam, a horn has value only on a living rhino - Yadava, Mahendra Kumar (Pachyderm, 2022)
On 22 September 2021 coinciding with World Rhino Day, 2,479 greater one-horned rhino horns were incinerated in Assam with full public participation in accordance with a decision taken by the State Government of Assam. The State government took this historic decision to send a strong message against wildlife crime and the illegal wildlife trade, especially the poaching of rhinos, and to strengthen the belief of the Assamese people that a rhino horn holds value only on a living rhino.